Knowledge, attitudes, and practices of nurses towards the prevention of pressure ulcers among bedridden patients at Entebbe Regional Referral Hospital, Wakiso District. A cross-sectional study. - Namusooko, Jemimah; Nalubega, Jane Frank; Nansereko, Hasifa; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David (Student’s Journal of Health Research Africa, 2025)
Background Pressure ulcers are localized injuries to the skin and underlying tissues primarily caused by prolonged pressure, shear, or friction. This aims to assess nurses’ knowledge, attitudes, and practices to identify gaps and develop targeted interventions. Methodology A cross-sectional study design that employed quantitative methods of data collection. This population included all Nurses at Entebbe Regional Referral Hospital who provide medical care to patients. A sample of 30 Nurses was selected using a simple random sampling technique. Results 20(67%) were females while 10(33%) were males. 12(40%) had a certificate as their highest level of education, 10(33%) were of diploma level, 8(27%) had a bachelor’s degree. 10(33%) mentioned that they identify a stage one pressure ulcer by redness on intact skin. 14 (47%) mentioned skin hygiene and barrier creams as the practice that helps them maintain skin integrity in bedridden patients. 14(47%) reported boosting immunity as the importance of hydration and protein in ulcer prevention. 12(40%) strongly believed that continuous education enhances their ability to prevent pressure ulcers effectively. 21(70%) rarely implemented repositioning schedules for bedridden patients. 12(40%) never performed a comprehensive skin inspection for bedridden patients. 22(73%) never used specialized pressure-relieving devices. Conclusion Nurses knew about the prevention of pressure ulcers, though with low attitudes and practices on target interventions. Recommendation Adopt evidence-based practices such as regular patient repositioning and comprehensive skin inspection. Increase efforts to educate caregivers on preventive measures to enhance continuity of care. Treat pressure ulcer prevention as an ethical responsibility and an integral part of nursing care.